1998
DOI: 10.1046/j.1471-4159.1998.71020875.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Neuropathologic Changes Induced by Central Injection of Carboxyl‐Terminal Fragment of β‐Amyloid Precursor Protein in Mice

Abstract: Abstract:Expression of the carboxyl-terminal fragment (CT) of the fl-amyloid precursor protein (APP) in transgenic animals has been linked with neurotoxicity. However, it remains to be clarified whether the neurotoxicity is caused by~3-amyloid proteins (A~3s) derived from CT or by CT itself. To study the in vivo neurotoxicity of CT, mice were given a single intracerebroventricular injection of a recombinant 105-amino acid CT (CT1C5; 68.5-685 pmol, intracerebroventricularly), anu changes in behavior and in brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 14 publications
5
35
0
Order By: Relevance
“…injection of CT105 (28). In this study, we confirmed that cued, spatial, and working memory also could be impaired by a single i.c.v.…”
Section: Discussionsupporting
confidence: 82%
“…injection of CT105 (28). In this study, we confirmed that cued, spatial, and working memory also could be impaired by a single i.c.v.…”
Section: Discussionsupporting
confidence: 82%
“…The acetylcholine level in the cerebral cortex and hippocampus was significantly decreased, accompanyied by reduction of mitochondrial pyruvate dehydrogenase activity (86). Also CTF induced reactive gliosis in the neocortex and hippocampus and neurodegeneration in the neocortex (85). These results indicate that centrally administered CTF induces behavioral impairment and neuropathologic changes, suggesting a direct toxic effect of CTF per se.…”
Section: Effects Of Ctf On the Calcium Homeostasis In The Neuronal Cellsmentioning
confidence: 85%
“…Learning and memory impairment and neuropathological changes in centrally injected CTF mice and Tg mice overexpressing CT100 and double Tg mice overexpressing CT100 and mutant tau CTF caused significant impairments in cued, spatial, and working memory performances in a dose-dependent manner following a single intracerebroventricular injection of CTF to mice (85,86). The acetylcholine level in the cerebral cortex and hippocampus was significantly decreased, accompanyied by reduction of mitochondrial pyruvate dehydrogenase activity (86).…”
Section: Effects Of Ctf On the Calcium Homeostasis In The Neuronal Cellsmentioning
confidence: 98%
“…Overexpression of β-CTF in neurons of transgenic mice led to hippocampal degeneration as well as deficits in memory and long-term potentiation [33,34].…”
Section: Discussionmentioning
confidence: 99%